When gradual change beats radical transformation : industrial companies may not be the face of digital disruption, but their evolutionary approaches to successful digital initiatives hold lessons for other sectors - Visnjic, Ivanka; Birkinshaw, Julian M.; Linz, Carsten (MIT Sloan Management Review, 2022)
Research into how some industrial companies have succeeded at digital transformation shows that those taking a steady, gradual approach may have the best results -- and the lessons learned apply across other sectors as well. The authors discuss the circumstances in which company leaders might be best served by taking a more incremental approach to digital business, and when they might choose to pursue a more revolutionary change.